Magnetic Resonance Imaging–Defined Osteophyte Presence and Concomitant Cartilage Damage in Knees With Incident Tibiofemoral Osteoarthritis: Data From the Pivotal Osteoarthritis Initiative Magnetic Resonance Imaging Analyses Study. Issue 9 (18th June 2022) - MacKay, James; Guermazi, Ali; Kwoh, C. Kent; See, P. L. Paul; Jarraya, Mohamed; Li, Ling; Hannon, Michael J.; Fuji, Tomoko; Roemer, Frank W.
Abstract : Objective: To describe compartmental frequencies of magnetic resonance image (MRI)–defined osteophytes and co‐localized cartilage damage and evaluate the associations of osteophyte size with any ipsicompartmental cartilage damage in knees with incident tibiofemoral radiographic knee osteoarthritis (OA). Methods: We evaluated knees from the Osteoarthritis Initiative without radiographic knee OA at baseline that developed radiographic knee OA during a 4‐year interval. Semiquantitative MRI scoring of osteophytes and cartilage damage was performed at the time point when radiographic knee OA was diagnosed, defined as Kellgren/Lawrence grade of ≥2, using the MRI Osteoarthritis Knee Score instrument. The frequencies of maximum osteophyte size and maximum grade of ipsicompartmental (i.e., patellofemoral, medial tibiofemoral, lateral tibiofemoral, posterior femur) cartilage damage were assessed. Generalized estimating equations were used to determine the association of MRI‐defined maximum osteophyte size with presence of any (excluding focal superficial defects) ipsicompartmental cartilage damage. Results: A total of 296 knees that did not have tibiofemoral radiographic knee OA at the baseline visit but developed radiographic knee OA during the 48‐month observational period were included. In the patellofemoral, medial tibiofemoral, and lateral tibiofemoral compartments, the most frequent osteophyte grade was 1 (67.6%, 59.1%, and 51.7%, respectively) and was 0 (51.7%) in the posterior femur. For all compartments except the posterior femur, a linear trend was found between increasing maximum osteophyte size and the presence of any concomitant cartilage damage. Conclusion: In this sample of knees with incident tibiofemoral radiographic knee OA, the patellofemoral joint showed more severe cartilage damage than other compartments regardless of concomitant osteophyte size. In the posterior femur, cartilage damage was rare despite the presence or size of concomitant osteophytes.